Efeitos da plataforma vibratória na histomorfometria e estresse oxidativo no músculo sóleo em ratos wistar obesos - Boaretto, Mariana Laís (2019)
Obesity negatively influences the musculoskeletal system and to prevent the comorbidities that this disease causes it is recommended to practice regular physical exercise. An exercise modality that is being used is the vibratory platform (PV) training, which seeks to improve muscle strength and potency. With this, the objective of this research was to verify effects of the vibratory platform in the soleus muscle in rats with obesity induced by monosodium glutamate (MSG). For this purpose, 32 Wistar rats were randomized equally to four groups: GC, GCP, GO, GOP. For the induction of obesity monosodium glutamate injections were used from the 1st to the 5th day of life of the animals. At 70 days old the training in PV was started. The protocol had a frequency adjusted at 60 Hz and amplitude of two millimeters, it was performed three times a week for 10 minutes over a period of eight consecutive weeks. At 130 days old, the animals were euthanized and the soleus muscles was collected for histological processing and histomorphometric analysis as the cross-sectional area, larger and smaller diameter of the muscle fiber, ratio of nuclei and blood vessels to muscle fiber, percentage of connective tissue, cross-sectional area, greater and smaller diameter of the neuromuscular junction and types of muscle fibers, besides the analysis of the activity of the enzymes cholinesterase (ChE), superoxide dismutase (SOD), catalase (CAT) and lipoperoxidation reaction (LPO). The data were statistically analyzed for their homogeneity, normality and analysis of the variance of two factors, adopting a level of significance of 5%. In the morphological analysis the obese groups presented muscular hypotrophy. In relation to the cross-sectional area, larger and smaller diameter, the GC and GO had higher avrage values when compared to the GCP and GOP. The capillary density and number of nuclei were lower in obese animals, but the mean was higher in the animals submitted to PV. The percentage of connective tissue was higher in obese animals, however the GOP presented smaller amount when compared to the GO. In the analysis of JNMs, concerning to the area, larger and smaller diameter, the GCP and GOP presented larger means when compared with the GC and GO, respectively. There was a predominance of oxidative fibers in the soleus muscle, with no differentiation of fibers in other types. In relation to oxidative stress, there was a decrease in lipoperoxidation in the obese groups, in the other SOD, CAT and ChE enzymes there was no significant difference. Therefore, it is concluded that the vibratory platform is able to promote changes in capillary density and nuclei by fiber, percentage of connective tissue, neuromuscular junctions and lipoperoxidation.